In vitro culture of coxsackievirus group B, type 3 immune spleen cells on infected endothelial cells and biological activity of the cultured cells in vivo. - Huber, S A (1984)
Spleen cells from male BALB/c mice infected 7 days earlier by an intraperitoneal injection of 3 X 10(4) PFU of a myocarditic strain of coxsackievirus B-3 lysed virus-infected endothelial cells in a 51Cr release assay. Cytotoxic activity in the in vivo sensitized spleen cell population could be further increased by culturing the immune spleen cells from infected mice on virus-infected or uninfected endothelial cells for 6 to 7 days in vitro. Cytotoxicity of in vitro cultured spleen cells to infected targets was mediated by T lymphocytes since reactivity was abolished by treatment of the spleen cells with anti-thy 1.2 serum and complement. Reciprocal assays with BALB/c and C57BL cells indicated that maximum cytotoxicity occurred when spleen cells were sensitized on syngeneic endothelial cells. Other experiments showed that spleen cells sensitized to coxsackievirus B-3 or encephalomyocarditis virus were selectively cytolytic to targets infected with the homologous virus. Adoptive transfer of T cells cultured in vitro on infected endothelial cells retained their ability to induce myocarditis in T-lymphocyte-deficient mice.